PENGARUH PENDEKATAN WRITING PROCESS TERHADAP KETERAMPILAN MENULIS OPINI SISWA SEKOLAH DASAR - Dinda Melinda; Dadan Djuanda; Diah Gusrayani (Jurnal Pena Ilmiah, 2022)
This study aims to determine the improvement of opinion writing skills of fourth grade elementary school students in the experimental class, improvement of opinion writing skills of fourth grade elementary school students in the control class, and determine the differences in the improvement of opinion writing skills of fourth grade elementary school students in the experimental class and control class. This research was conducted through a quasi-experimental method with a nonequivalent control group design. The research population is fourth grade elementary school students in Jatinunggal District. The research sample is the fourth grade students of SDN Bunisari and SDN Cirayun. The instruments used were in the form of opinion writing skills tests and observation sheets. The results of the study show that: 1) learning carried out in the experimental class using the writing process approach provides an increase in students' opinion writing skills; 2) learning in the control class, namely through conventional learning affects the improvement of students' opinion writing skills, there is no difference; 3) the students' opinion writing skills in the experimental class and the control class have significant differences.